Understanding Patients' Perspectives on Opt-Out, Incentivized, and Mandatory HIV Testing - Noland, Carey M; Vaughn, Nicole A; Sun, Sirena; Schlecht, Hans P (International Journal of Health Sciences, 2015)
Background: Currently, widespread HIV testing is the best preventive action against further spread of the HIV epidemic. However, over 40% of the U.S. population has never been tested for HIV and 25% of those with HIV have never been tested. To increase testing rates, in 2006 the CDC advised healthcare settings to conduct testing on an opt-out basis. Methods: Qualitative, semi-structured interviews with ten seropositive patients and ten seronegative were conducted to address the lack of studies investigating patients’ acceptance of and attitude towards this and more novel testing models, e.g. incentivized or anonymous mandatory testing. Participants were asked about their HIV testing history and attitudes towards opt-out, incentivized, and mandatory anonymous HIV testing. Results: Major themes were identified using grounded theory data analysis. All participants were receptive to opt-out testing, and saw the removal of separate written consent as beneficial as long as patients were given the opportunity to consent in some form. Conclusion: Ultimately, both mandatory and opt-out testing were equally indicated by participants as being the most effective testing model at increasing testing rates. A firm understanding of patients’ perspectives allows for development of effective HIV testing initiatives that are patient-sensitive and can substantially reduce HIV infection rates. Keywords: HIV testing, opt-out HIV testing, incentivized HIV testing, mandatory HIV testing, patient education.